Biological response of extracorporeal shock wave therapy to tendinopathy in vivo (review) - Chen, Yixuan; Lyu, Kexin; Lu, Jingwei; Jiang, Li; Zhu, Bin; Liu, Xueli; Li, Yujie; Liu, Xinyue; Long, Longhai; Wang, Xiaoqiang; Xu, Houping; Wang, Dingxuan; et al. (Frontiers in Veterinary Science, 2022)
Tendinopathy is a degenerative disease of the tendons caused by prolonged overstretching or overuse of the tendons. It accounts for a large proportion of musculoskeletal disorders which can occur in all age groups. The management of tendinopathy is typically conservative. In clinical practice, when other conservative treatments fail, extracorporeal shock wave therapy (ESWT) is normally used as an efficient alternative to surgical management. A number of basic studies have shown that ESWT with lower energy flux densities can produce some biological responses in vivo to tendinopathy and may accelerate the initiation of the healing process in injured tendons. ESWT has a positive impact on the interactive chain of biological response, enhancing the signaling pathways of angiogenesis through mechanical conduction, promoting cell proliferation and collagen formation. Finally, it helps tissue regeneration by controlling inflammation. The purpose of this review is to summarize the biological responses generated by ESWT in tendinopathy through a comprehensive review of the published literature. Although ESWT has been used clinically for the treatment of tendinopathies for nearly decades, less is known about the experimental studies of its biological effects on tendon tissue. Further studies on the biological response of ESWT for tendon injuries in vivo are needed in the future in order to provide better management to patients.